Modern features of varicella encephalitis in children - N. V. Scripchenko; G. P. Ivanova; V. N. Komantsev; M. V. Savina (Журнал инфектологии, 2014)
There was conducted a survey among 65 children aged from 1 year to 17 with varicella encephalitis. There was determined predominance of cerebellar forms of the disease, in 93,9%, that is characterized by the development of the light pyramidal disorders on the contrast to the cerebral that is characterized by the development of convulsivecomatose syndrome. It was determined that the disease is distinguished by the rareness of the detected changes on the MRI, 12,3% only. It was detected that the changes of the evoked potentials could be seen among all the patients and are characterized by the predominance demyelinating changes of the brainstem structures when having a cerebellar form and neuronal disorders of the cerebral hemisphere when having a cerebral form. The outcome of the cerebellar form is recovery in 100% of cases, and in cerebral – the development of epilepsy was detected in 50% and death in 25%.